Analysis of effects of macroscopic propagation and multiple molecular orbitals on the minimum in high-order harmonic generation of aligned CO2 - Jin, Cheng; Le, Anh-Thu; Lin, C. D. (My University, 2011)
We report theoretical calculations of the effect of the multiple-orbital contribution in high-order harmonic generation (HHG) of aligned CO2 with the inclusion of macroscopic propagation of harmonic fields in the medium. Our results show very good agreement with recent experiments for the dynamics of the minimum in HHG spectra as laser intensity or alignment angle changes. Calculations are carried out to check how the position of the minimum in HHG spectra depends on the degrees of molecular alignment, laser-focusing conditions, and the effects of alignment-dependent ionization rates of the different molecular orbitals. These analyses help to explain why the minima observed in different experiments may vary.